2020
DOI: 10.1002/acr.23859
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Economic Evaluations of Cycling Versus Swapping Medications in Patients With Rheumatoid Arthritis After Failure to Respond to Tumor Necrosis Factor Inhibitors

Abstract: Objective To systematically review the modeling approaches and quality of economic analyses comparing cycling tumor necrosis factor inhibitors (TNFi) to swapping to a therapy with a different mode of action in patients with rheumatoid arthritis whose initial TNFi failed. Methods We searched electronic databases, gray literature, and references of included publications until July 2017. Two reviewers independently screened citations. Reporting quality was assessed using the Consolidated Health Economic Evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…82 , 83 Anti-TNFs were reported to have the lowest costs and highest quality-adjusted life-year (QALYs) ( vs other biologics), and were deemed to be the most cost-effective treatment option in RA. 83 Using a US-based administrative-claims database, Karpes Matusevich et al 19 reported that swapping to non-anti-TNF targeted agents was cost-effective at the US$100,000 per QALY threshold following failure of anti-TNF treatment in patients with RA, although differences in the design, key assumptions, and model structure chosen had a major impact on the individual study conclusions. This study highlighted the need for further studies to evaluate cost-effectiveness with switching choices other than rituximab or IV abatacept, to better reflect current clinical practices, of longer-term studies on the progression of RA, of RA costs over time and for greater standardisation and transparency in the reporting of economic evaluation studies.…”
Section: Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…82 , 83 Anti-TNFs were reported to have the lowest costs and highest quality-adjusted life-year (QALYs) ( vs other biologics), and were deemed to be the most cost-effective treatment option in RA. 83 Using a US-based administrative-claims database, Karpes Matusevich et al 19 reported that swapping to non-anti-TNF targeted agents was cost-effective at the US$100,000 per QALY threshold following failure of anti-TNF treatment in patients with RA, although differences in the design, key assumptions, and model structure chosen had a major impact on the individual study conclusions. This study highlighted the need for further studies to evaluate cost-effectiveness with switching choices other than rituximab or IV abatacept, to better reflect current clinical practices, of longer-term studies on the progression of RA, of RA costs over time and for greater standardisation and transparency in the reporting of economic evaluation studies.…”
Section: Biomarkersmentioning
confidence: 99%
“…1 The European League Against Rheumatism (EULAR) recommends a treat-totarget strategy aiming for sustained clinical remission (or low disease activity) recommending 1 Historically, anti-TNFs have accounted for the majority of first-line biological therapies for RA, which may have increased further due to their increased cost-effectiveness following the introduction of biosimilars. 17,18 However, 30-40% of patients with RA discontinue anti-TNFs due to primary IR (lack of response identified following initial dosing), secondary IR (reduction in initial response over time) or intolerance; 1,19,20 each situation necessitates a change in treatment regimen.…”
Section: Introductionmentioning
confidence: 99%